Peningkatan pemahaman mata pelajaran ipas materi indonesiaku kaya raya melalui model problem based learning pada kelas v sekolah dasar - Ardhana, Bima Kusuma; Istiyati, Siti; Adi, Fadhil Purnama (Universitas Sebelas Maret, 2025)
This research aims to increase understanding of science and science learning material on Indonesia Kaya Raya by using the Problem Based Learning learning model for class students at SD Negeri 2 Kuwarisan Kebumen. This research is a classroom action research (PTK). This research was carried out through two cycles. Each cycle has two meetings. Every meeting contains observation, planning, action, reflection. The subjects of this research were class V students at SD Negeri 2 Kuwarisan. Data collection techniques include interviews, observation, documentation and tests. The validity test technique uses triangulation techniques. The data analysis used in this research is data analysis according to Sugiyono. Data analysis begins with data collection, data reduction, data presentation and drawing data conclusions. The results of the research show an increase in understanding of Indonesia Kaya Raya material by using the Problem Based Learning learning model. This can be proven by the increase in the percentage of students who meet the minimum completeness criteria (KKM) at the pre-action stage by 22% or there are 2 students. Meanwhile, 78% of students have not met the minimum completeness criteria (KKM), or there are 7 students. In cycle I, 66.6% of students met the minimum completeness criteria (KKM), or there were 6 students. Meanwhile, 33.3% or 3 students have not reached the minimum completion criteria (KKM). In cycle II, there were 11.1% or 1 student who had not met the minimum completeness criteria (KKM), while 88.8% or 8 students had met the minimum completeness criteria (KKM). The conclusion based on this research is that using the Problem Based Learning learning model can increase understanding of the wealth of Indonesian science and science learning material.